THE INFLUENCE OF USING SAP CRM ON INCREASING CUSTOMER SATISFACTION INDEX AT PT. BANK X IN MEDAN, INDONESIA - Erwin Abu BAKAR; Iskandar MUDA; Novi Natalia PADANG; Alexandru NEDELEA; Mazli M. WARDHANI (USV Annals of Economics and Public Administration, 2021)
This paper aims to examine various concepts related to the development of definitions and dimensions of customer relationship management, and to try to develop a comprehensive model of customer relationship management, especially at PT. Bank X. The problems that will be raised in this paper are how to develop concepts, definitions and dimensions of customer relationship management and second, how to develop a model of customer relationship management that can be applied to PT. Bank X. The approach used in writing this paper is a qualitative approach, namely the research method used to examine scientific objects. The academic implication in this paper is that there is a theoretical understanding of the causes of company success and failure in implementing System Application and Processing Customer Relationship Management (SAP-CRM). Meanwhile, the practical implications for this journal are expected to be taken into consideration for business people, especially in the banking services industry in implementing SAP-CRM. The conceptual focus developed in this paper is to examine the dimensions of customer relationship management so that a model that describes customer relationship management in the banking sector can be developed. The original contribution to this journal writing can provide a new perspective on a more proactive CRM.